Pulmonary endarterectomy in patients with antiphospholipid syndrome-associated chronic thromboembolic pulmonary hypertension - KOCAKAYA, DERYA; ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER; YILDIZELİ, BEDRETTİN; İNANÇ, GÜZİDE NEVSUN (My University, 2022)
Background: Antiphospholipid syndrome is an autoimmune disease characterized by the occurrence of venous and/or arterial thrombosis. Chronic thromboembolism is one of the known established pathogenesis of pulmonary hypertension, known as chronic thromboembolic pulmonary hypertension. Pulmonary endarterectomy is the treatment of choice for chronic thromboembolic pulmonary hypertension. The aim of this study is to evaluate the efficacy and risk of pulmonary endarterectomy in patients with antiphospholipid syndrome-associated chronic thromboembolic pulmonary hypertension. Methods: Data were prospectively collected and retrospectively analyzed, for patients who underwent pulmonary endarterectomy between March 2011 and March 2020. Results: Seventeen patients (4 male and 13 female) were identified. Thirteen patients had primary antiphospholipid syndrome and 4 had secondary antiphospholipid syndrome. The mean age was 34.82 ± 10.07 years and the mean time interval between the diagnosis and surgery was 26.94 ± 17.35 months. Dyspnea on exertion was the main symptom in all patients. Seven patients had previous deep vein thrombosis, 5 patients had a history of recurrent abortions, and 2 patients had hemoptysis. Following surgery, mean pulmonary artery pressure decreased from 47.82 ± 13.11 mm Hg to 22.24 ± 4.56 mm Hg (P < .001), and pulmonary vascular resistance improved from 756.50 ± 393.91 dyn/s/cm−5 to 298.31 ± 132.84 dyn/s/cm−5 (P < .001). There was no in-hospital mortality with a mean follow-up of 75.29 ± 40.21 months. The functional capacity of all patients improved from 269.46 ± 111.7 m to 490 ± 105.34 m on a 6-minute walking test. Conclusions: Pulmonary endarterectomy is a safe and curative treatment in patients with antiphospholipid syndrome-associated chronic thromboembolic pulmonary hypertension. It has a favorable outcome by increasing the quality of life. A multidisciplinary experienced chronic thromboembolic pulmonary hypertension team is critical in the management of these unique patients
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Antiphospholipid syndrome; chronic thromboembolic pulmonary hypertension; pulmonary endarterectomy; outcome; SYSTEMIC-LUPUS-ERYTHEMATOSUS; INTERNATIONAL CONSENSUS STATEMENT; CLASSIFICATION CRITERIA; ANTIBODIES; ANTICOAGULANT; MANAGEMENT; THROMBOSIS; DIAGNOSIS; Antiphospholipid syndrome; chronic thromboembolic pulmonary hypertension; pulmonary endarterectomy; outcome